A monoclonal antibody to Candida albicans enhances mouse neutrophil candidacidal activity. - Caesar-TonThat, T C (1997)
A monoclonal antibody (MAb) to Candida albicans (MAb B6.1) that protects against candidiasis and the nonprotective MAb B6 were compared for ability to support neutrophil (polymorphonuclear leukocyte [PMN]) candidacidal activity. Both MAbs are immunoglobulin M, and each recognizes distinct C. albicans mannan cell wall determinants. PMN candidacidal activity was assessed by transmission electron microscopy and by an in vitro killing assay. The results indicated that MAb B6.1, but not MAb B6, enhances ingestion and killing of yeast cells by PMN in the presence of serum complement.